Knowledge, Perception and Attitude of Users with Visual Impairment on E-Banking Systems in Nigeria - Jamal Abioye Adio; Sunday Abimbola Abodunrin; Rasheed Adekunle Abilu (Utan Kayu Publishing, 2026)
The rapid expansion of digital banking services has increased accessibility and convenience for users, including persons with disabilities. This study investigated the knowledge, perception, and attitudes of users with visual impairment towards e-banking systems in Oyo State, Nigeria. Specifically, the study examined the relationship among knowledge, perception, accessibility, and attitudes towards e-banking among users with visual impairment. A descriptive survey research design was adopted for the study. Purposive sampling technique was used to select 47 respondents with visual impairment comprising 24 males and 23 females. Data were collected using a structured questionnaire and analysed using descriptive and inferential statistics, including mean, standard deviation, and Pearson Product Moment Correlation (PPMC). The findings revealed a significant relationship between accessibility and usability of e-banking platforms among users with visual impairment. The study further showed that although respondents demonstrated awareness of e-banking services, challenges relating to accessibility, screen-reader compatibility, digital literacy, and transaction security still affect effective utilization. The study recommends that financial institutions should organize specialized digital literacy training for users with visual impairment, improve compatibility of e-banking applications with screen readers and voice-assisted technologies, strengthen transaction security through audio-based verification and multi-factor authentication, and develop more inclusive and accessible e-banking platforms.